Introduction to "Twenty Five Years of Modern Tsunami Science Following the 1992 Nicaragua and Flores Island Tsunamis, Volume II" - Kanoglu, Utku (2020)
Following the first volume (PAGEOPH, 2019, 176, No. 7), twenty-four papers on tsunamis are included in the PAGEOPH topical issue "Twenty five years of modern tsunami science following the 1992 Nicaragua and Flores Island tsunamis: Volume II,'' reporting on the frontiers of tsunami science and research. The first two papers overview meteorological tsunamis, discussing progress since the 1992 Daytona event, and examining the March 2017 Persian Gulf destructive event. The next four papers review historical tsunami events, starting with a paper providing statistics for the last 120 years. The 2018 Kodiak event is investigated in the following two papers. A set of five papers discusses tsunami-warning methodologies specifically for the Australia and Nankai (Japan) regions, and general tsunami warning approaches. Probabilistic tsunami hazard assessment including case studies for two Australian coasts and the Pacific Coast of Central America, as well as discussion regarding the effect of shallow slip amplification uncertainty, and tsunami hazard assessment for the Port of Ensenada, Baja California, are presented in the next five papers. Two papers discuss tsunami tide interaction, and the following two investigate landslide-generated tsunamis, specifically a tsunami landslide scenario study for the Maltese Islands, and the 1694 Ambon, Indonesia tsunami. Tsunami hydrodynamics studies investigating shoaling on steep continental slopes and transmission of long surface, and tsunami-like waves are presented in the last two papers.